The impact of demographic trends on economic growth ? productivity in Pakistan (1980-2007) - Khalid Zaman,; Waseem Ikram,; Mehboob Ahmad, (Sunway University College, 2009)
This paper seeks to examine the impact of demographic variables on economic growth in Pakistan. A long-run relationship between the variables has been found by applying Johanson?s Co-integration Technique after finding the series I(1). The Error Correction Model (ECM) has been applied to streamline the short-run and long- run impacts of the variables on economic growth. Population has a positive but decreasing impact on economic growth in the long run. Trade liberalisation and Human Capital Formation have a negative impact on globalisation in the long run and an insignificant impact in the short run. As a result of an increase in unemployment in the labour market in the short run, Life Expectancy, Labour Productivity Per Capita and Population Growth Rate have a negative impact on economic growth. This analysis will help decision makers in developing strategies and policies to accelerate economic growth, human capital formation and trade liberalisation in Pakistan.